Trabeculectomy with double low dose of mitomycin C – two years of follow-up - Errico, Donato (Dove Medical Press, 2011)
PURPOSE: To evaluate the efficacy and the safety of a surgical technique in which classic trabeculectomy ab externo is performed with a double application of low-dose mitomycin C (MMC) in uncontrolled open-angle glaucoma (OAG) patients. METHOD: A consecutive series of 43 white patients (43 eyes) with uncontrolled primary OAG underwent trabeculectomy surgery. A double application of MMC (0.1%) was performed: the first under the Tenon’s capsule for 3 minutes, and the second below the scleral flap for 1 or 2 minutes, according to the risk factors. Complete success was defined as intraocular pressure (IOP) <14 mmHg without any additional glaucoma surgery or medication. Qualified success was defined as IOP <14 mmHg with additional needling revision. RESULTS: Mean preoperative IOP was 29.9 mmHg (SD 3.8) for all eyes evaluated. At 1 day postoperative, mean IOP was 6.7 mmHg (SD 1.26). At the end of the first 2 weeks postoperative, mean IOP was 8.6 mmHg (SD 1.7), at 12 months mean IOP was 11.3 mmHg (SD 1.4; P < 0.0001) and at 24 months mean IOP was 11.4 mmHg (SD 1.5; P < 0.0001). At 3 months, two eyes (5.4%) underwent needling of the bleb for cystic blebs formation. CONCLUSION: In this study we presented the results after 2 years of follow-up of OAG undergoing trabeculectomy with dual administration of MMC (0.1 mg/mL). After 24 months, complete success was achieved in 93% of patients and a qualified success in 100% of patients.